Effects of Periplasmic Chaperones and Membrane Thickness on BamA-Catalyzed Outer-Membrane Protein Folding. Issue 23 (24th November 2017) - Schiffrin, Bob; Calabrese, Antonio N.; Higgins, Anna J.; Humes, Julia R.; Ashcroft, Alison E.; Kalli, Antreas C.; Brockwell, David J.; Radford, Sheena E.
Abstract: The biogenesis of outer-membrane proteins (OMPs) in gram-negative bacteria involves delivery by periplasmic chaperones to the β-barrel assembly machinery (BAM), which catalyzes OMP insertion into the outer membrane. Here, we examine the effects of membrane thickness, the Escherichia coli periplasmic chaperones Skp and SurA, and BamA, the central subunit of the BAM complex, on the folding kinetics of a model OMP (tOmpA) using fluorescence spectroscopy, native mass spectrometry, and molecular dynamics simulations. We show that prefolded BamA promotes the release of tOmpA from Skp despite the nM affinity of the Skp:tOmpA complex. This activity is located in the BamA β-barrel domain, but is greater when full-length BamA is present, indicating that both the β-barrel and polypeptide transport-associated (POTRA) domains are required for maximal activity. By contrast, SurA is unable to release tOmpA from Skp, providing direct evidence against a sequential chaperone model. By varying lipid acyl chain length in synthetic liposomes we show that BamA has a greater catalytic effect on tOmpA folding in thicker bilayers, suggesting that BAM catalysis involves lowering of the kinetic barrier imposed by the hydrophobic thickness of the membrane. Consistent with this, molecular dynamics simulations reveal that increases in membrane thinning/disorder by the transmembrane domain of BamA is greatest in thicker bilayers. Finally, we demonstrate that cross-linking of the BamA barrel does not affect tOmpA folding kinetics in 1, 2-dimyristoyl- sn -glycero-3-phosphocholine (DMPC) liposomes, suggesting that lateral gating of the BamA barrel and/or hybrid barrel formation is not required, at least for the assembly of a small 8-stranded OMP in vitro . Graphical abstract: Image 1 Highlights: Mechanisms of OMP periplasmic transport and folding by BAM are poorly understood. BamA catalyzes folding by reducing the kinetic barrier imposed by membrane thickness. BamA proteoliposomes promote folding of Skp-bound tOmpA. Lateral gating is not required for BamA-catalyzed folding of tOmpA in DMPC bilayers.